SEBARAN SPASIAL PEDAGANG KOMODITAS LOKAL DAN JANGKAUAN LAYANAN PASAR YOUTEFA: KAJIAN SPASIAL DAN EKONOMI LOKAL - Yanthy, Normalia Ode; Erelak, Ekiles; M Labok, Anna (DINAMIS, 2025)
Youtefa Market is a key node of the local economy in Jayapura City, accommodating traders of local commodities and Papuan handicrafts. This study aims to: (1) map the spatial distribution of traders’ places of origin, (2) analyze the market’s service coverage, and (3) identify the main factors influencing traders’ choice of selling location. A descriptive quantitative approach was employed through trader surveys, field observations, and documentation, which were then analyzed using Geographic Information System (GIS)–based spatial analysis and network analysis. The results show that Youtefa Market serves areas extending to agrarian hinterlands and coastal regions, with the highest concentration of traders located within a radius of less than 5 km from the market. Travel time analysis indicates that most traders spend less than 30 minutes to reach the market, while those from agrarian and coastal areas experience longer travel times and higher transportation costs. Youtefa Market is chosen due to a combination of good accessibility, large potential customer base, relatively low operating costs, and strong social networks, particularly among Indigenous Papuan traders. These findings confirm the role of Youtefa Market as a regional distribution center as well as a socio-economic infrastructure that connects agrarian and coastal production systems with urban consumption. Consequently, policies related to market management and potential relocation should be based on spatial service-area analysis, improved accessibility, and secure trading spaces to ensure the sustainability of micro-enterprises and local economic networks.